MISKONSEPSI TUKANG BANGUNAN DALAM TEKNIK MEMBANGUN KONSTRUKSI TAHAN GEMPA - Dalil Herman, Nanag (TERAS)
This article is taken from a small section of the dissertation research, about development of a model program to improve the competence of transmigrantion community through the pottential environment based training. This paper will only present a small description of the research, that is concerning misconceptions of the workers / builders as a research subject, the technical knowledge to build earthquake-resistant housing construction. Research done by a "Research Development." The results obtained from the implementation of pilot training model, with the aim of knowing implementing and functioning of the learning program in training of on the construction of earthquake resistant.